Varying cognitive targets and response rates to enhance the question-behaviour effect: An 8-arm Randomized Controlled Trial on influenza vaccination uptake. (May 2017) - Conner, Mark; Sandberg, Tracy; Nekitsing, Chandani; Hutter, Russell; Wood, Chantelle; Jackson, Cath; Godin, Gaston; Sheeran, Paschal
Abstract: Rationale: The question-behaviour effect (QBE) refers to the finding that survey questions about a behaviour can change that behaviour. However, little research has tested how the QBE can be maximized in behavioural medicine settings. The present research tested manipulations of cognitive targets (questions about anticipated regret or beneficence) and survey return rates (presence vs. absence of a sticky note requesting completion of the questionnaire) on the magnitude of the QBE for influenza vaccination in older adults. Method: Participants ( N = 13, 803) were recruited from general practice and randomly allocated to one of eight conditions: control 1 (no questionnaire); control 2 (demographics questionnaire); intention and attitude questionnaire (with or without a sticky note); intention and attitude plus anticipated regret questionnaire (with or without a sticky note); intention and attitude plus beneficence questionnaire (with or without a sticky note). Objective records of subsequent influenza vaccination from general practice records formed the dependent variable. Results: Intention-to-treat analyses indicated that receiving an influenza vaccination questionnaire significantly increased vaccination rates compared to the no questionnaire, OR = 1.17, 95% CI = 1.01, 1.36 and combined control conditions, OR = 1.13, 95% CI = 1.01, 1.25. Including the sticky note significantly increased questionnaire return rates, OR = 1.25, 95% CI = 1.04, 1.50. However, there were no differences in vaccination rates between questionnaires containing different cognitive targets, a sticky note or not, and no interactions. There were no significant differences in the per-protocol analyses, i.e. among respondents who completed and returned the questionnaires. Conclusion: The QBE is a simple, low-cost intervention to increase influenza vaccination rates. Increasing questionnaire return rates or asking anticipated regret or beneficence questions in addition to intention and attitude questions did not enhance the QBE. Highlights: Receiving an influenza questionnaire significantly increased vaccination rates. Questionnaires on different cognitions did not differentially affect vaccination. A sticky note help request significantly increased questionnaire return rates. A sticky note help request did not increase vaccination rates.